Prosthetic dental management of a patient with anhidrotic ectodermal dysplasia. A Case Report. - Daniel Hernández-González; Jennifer Orozco-Páez (Universidad de Concepción., 2021)
Introduction: Ectodermal dysplasia (ED) comprises a broad group of genetic disorders characterized by alterations of the structures derived from the ectoderm, including those of the stomatognathic system. Case Report: The present article aims to report the prosthetic management of a patient with anhidrotic ectodermal dysplasia. A male patient diagnosed with ED who attended the dental consultation displaying oligodontia; underdeveloped alveolar ridges were observed. Results: The established treatment consisted of the adaptation of implant-supported fixed full-arch prosthesis designed through CAD-CAM technology for the lower jaw and of a removable partial prosthesis with muco-dental support for the upper jaw. The dental approach of patients with ED is based on a correct analysis of the facial characteristics and stomatological conditions of each subject. Conclusion: A multidisciplinary approach is mandatory due to the biological and functional complexity in biomechanical terms of these individuals.